1981
DOI: 10.1111/j.1651-2227.1981.tb16553.x
|View full text |Cite
|
Sign up to set email alerts
|

Passage of Cephalosporins and Amoxicillin Into the Breast Milk

Abstract: The concentrations of five cephalosporins and amoxicillin in breast milk were studied in 42 voluntarily participating lactating mothers using standard assay methods. Each mother received one single dose of 1 g of either an orally or intravenously administered antibiotic. Amoxicillin, cephalexin, and cefadroxil were given orally, and peak milk concentrations averaged 0.81 +/- 0.33 microgram/ml at 5 hours, 0.50 +/- 0.23 microgram/ml at 4 hours, and 1.64 +/- 0.73 microgram/ml at 6 hours, respectively. Cephalothin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 4 publications
1
31
0
1
Order By: Relevance
“…Although cephalosporins, penicillins, and ACE-inhibitors such as captopril have been detected in breast milk after oral administration to lactating mothers (24), their concentrations in milk are comparatively low. Regardless of the route of transport of this drug across the gland into milk, the presence of PEPT2 in the epithelial cells would provide an efficient pathway for reabsorption of the peptidomimetics back into the gland tissue to reduce the burden of the milk.…”
Section: Discussionmentioning
confidence: 99%
“…Although cephalosporins, penicillins, and ACE-inhibitors such as captopril have been detected in breast milk after oral administration to lactating mothers (24), their concentrations in milk are comparatively low. Regardless of the route of transport of this drug across the gland into milk, the presence of PEPT2 in the epithelial cells would provide an efficient pathway for reabsorption of the peptidomimetics back into the gland tissue to reduce the burden of the milk.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the infant mice were born to a mother with an altered intestinal microbiota. Although the infants may experience limited exposure to antibiotics during nursing, the levels transferred into milk are quite low and subtherapeutic (30)(31)(32). There were no appreciable differences in the size of litters or weights of infant mice between MAT and CTRL groups, nor did any adult mice treated with antibiotics exhibit signs of dehydration or weight loss.…”
Section: Mat Causes Reproducible Shifts In the Intestinal Microbiota mentioning
confidence: 99%
“…Following administration of cephalothin by intravenous route Bergan (1987) and Kafetzis et al (1981) found C max in milk at 1 and 2 hours, respectively. In our work C max is achived between the first and the second hour postadministration of the drug.…”
Section: Resultsmentioning
confidence: 99%